The Others and the Croats in Early Medieval Eastern Adriatic History - Ivan Majnarić ([sic])
This paper examines the narrative strategies of the oldest two medieval Eastern Adriatic historical accounts regarding the emergence of the Early Medieval gentes in local history. Seen through the framework of Othering, these accounts display complicated images within images rather than a linear narrative. At the same time, two categories of the Other seem to appear in them – the present, preferable Other, and the past, undesirable Other. By employing such strategies, the two histories depict all the gentes in an almost identical manner, and in accordance with the established images, with only some layers of actual historical background.Keywords: Middle Ages, Eastern Adriatic, medieval historians, Others, Croats“… multi christianorum … eligentes magis cum eis sustinere persecutiones et penuriam et salvare animas suas, quam gaudere ad tempus cum gentilibus et vi eorum perdere animas” (CPD 1: 28-30). Such severe accusations were brought in historical accounts from the High Middle Ages against those wicked gentes that were, at some point during the Migration Period, disturbing the “peacefully living” urban population of the Eastern Adriatic. Did the events mentioned in them really happen? If not, what was the point of a medieval historiographical narrative? Who were the gentes of those “dark ages,” especially from the viewpoint of the High Medieval histories? To answer these questions in the following text, I will employ one among a variety of useful frameworks for understanding Early Medieval history of the Eastern Adriatic – that of Othering. To put it simply, Othering can be understood as a binary dichotomy of interrelationships between persons, social groups, and/or identities in dominant and inferior cultural positions, in which the notion of belonging becomes a crucial sign of one’s social position. In such a formation of the Self and the Other, the process of the Othering provides evidence of the fashioning of the Self, its hidden desires and goals, through the stereotyping and scapegoating of the Other – weather positively or negatively – and by being aware of the Other. In fact, the Self is revealed and constructed through the Other and in relation to the Other. In such a dynamic, the value judgment of the Other varies over time between inferior (most often) and equal. Depending on how distant they are from the Self, there can be more than one Other, although they are to some extent all the same because of their Otherness. The concept can be deployed in many ways, one of which is also the construction of the identity/ethnicity, particularly suitable in this case. It is also a useful tool primarily in postcolonial medieval studies (or postcolonial theory applied to medieval societies). Although such use has been much debated, it seems to serve the purpose of interpreting various medieval cultural and social contacts, confrontation, and exchange (above all transculturation and hybridity), as well as medieval narratives. I will proceed to examine the narratives of the two oldest historical accounts from the Eastern Adriatic area – Gesta Regum Sclavorum (CPD; also called Chronicle of the Priest of Diocleia) and Historia Salonitana (HS) – about the Migration Period, with a focus on the emergence of Croats in the history of South-Eastern Europe. I aim to demonstrate the manner in which medieval historians used multi-layered strategies of Othering to present the past in a hierarchical order corresponding to the needs of their present. By doing so, two categories of the Other seem to appear – the present, preferable Other, and the past, undesirable Other. I hope that I will, at the same time, promote a more thorough (inter)textual analysis of the narrative corpora and symbol structures of both Eastern Adriatic medieval histories, as medievalist